A Carrier-Based Phase-Shift Space Vector Modulation Strategy for a Nine-Switch Inverter - Neerakorn Jarutus (2018)
© 2016 IEEE. By using a carrier-based pulse width modulation, this paper presents a developed phase-shift space vector modulation strategy for a nine-switch inverter to overcome one of major drawbacks, i.e., output voltage and current distortion. This is due to the crossover of modulating waves per phase based on the different phase-shift angle between dual terminals. The proposed strategy done by mathematical algorithms based on the critical operating point principle accomplishes in the wide range of phase-shift conditions that contribute in both common-and difference-frequency modes with its expediency of uncomplicated computation and handy implementation. Even more, the identical and nonidentical modulation index techniques are wholly brought up. The feasibility of the proposed strategy is confirmed by results of the simulation directly compared with the experiment, showing in good accordance with the theoretic analysis.